2019
DOI: 10.1097/rlu.0000000000002641
|View full text |Cite
|
Sign up to set email alerts
|

18F-Fluciclovine PET/CT in Suspected Residual or Recurrent High-Grade Glioma

Abstract: Purpose To retrospectively investigate the uptake of 18F-fluciclovine on PET/CT in patients with suspected recurrent high-grade glioma (HGG). Methods Twenty-one patients were included. The standard of truth was histopathologic interpretation if available. When histopathology was not available or rebiopsy did not show signs of malignancy, clinical follow-up including MRI and clinical outcome was considered the standard of truth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 33 publications
4
41
0
1
Order By: Relevance
“…F-Fluciclovine images showed high contrast, confirmed by the high tumor-to-brain ratios (tumor SUVmax-to-SUVmean of a reference normal-brain region), concordant with the first clinical studies [10][11][12][13][14]. Our results showed that the two ratios calculated with two different reference regions (either the contralateral normal brain tissue or the cerebellum) are highly correlated, as was previously described by Kondo et al [10].…”
supporting
confidence: 91%
See 1 more Smart Citation
“…F-Fluciclovine images showed high contrast, confirmed by the high tumor-to-brain ratios (tumor SUVmax-to-SUVmean of a reference normal-brain region), concordant with the first clinical studies [10][11][12][13][14]. Our results showed that the two ratios calculated with two different reference regions (either the contralateral normal brain tissue or the cerebellum) are highly correlated, as was previously described by Kondo et al [10].…”
supporting
confidence: 91%
“…Recently, Tsuyuguchi et al showed in a preliminary study of six patients that 18 F-Fluciclovine may provide better assessment than 11 C-Methionine for the initial detection of glioma [13]. Furthermore, 18 F-Fluciclovine may be a promising tracer to detect high grade recurrent gliomas [14].…”
Section: Introductionmentioning
confidence: 99%
“…Bashir et al [ 27 ] found that a 20-min 18 F-FET PET scan is a powerful tool with TBRmax (sensitivity 99%, specificity 94%) to distinguish posttreatment changes from recurrent glioblastoma 6 months postradiotherapy. Bogsrud et al [ 28 ] reported the performance of a new type of amino acid 18 F-fluciclovine in PET/CT of suspected residual or recurrent glioma, but the ability of 18 F-fluciclovine PET/CT to discriminate between recurrent glioma and treatment-related changes could not be determined because no patients had confirmed treatment-related changes. More recently, 18 F-labelled DOPA is a more widely used amino acid tracer than 11 C-MET because it has a longer half-life of up to 110 min, whereas that of 11 C-MET is only 20 min.…”
Section: Discussionmentioning
confidence: 99%
“…Bashir et al [27] found that a 20-minute 18 F-FET PET scan is a powerful tool with TBRmax (sensitivity 99%, speci city 94%) to distinguish posttreatment changes from recurrent glioblastoma 6 months postradiotherapy. Bogsrud et al [28] reported the performance of a new type of amino acid 18 F-uciclovine in PET/CT of suspected residual or recurrent glioma, but the ability of 18 F-uciclovine PET/CT to discriminate between recurrent glioma and treatment-related changes could not be determined because no patients had con rmed treatment-related changes. More recently, 18 F-labelled DOPA is a more widely used amino acid tracer than 11 C-MET because it has a longer half-life of up to 110 minutes, whereas that of 11 C-MET is only 20 minutes.…”
Section: Discussionmentioning
confidence: 99%